Pengaruh Brain Circulation untuk Memperkuat Pasar Tenaga Kerja dalam Masyarakat ASEAN 2015 - Darmawan, Arif; Desiera, Qisty Anzilni (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2014)
ASEAN Community 2015 became one of its own products made by ASEAN leaders to ease the creation of a variety of access both in the economic, political, social, cultural, defense and security. Within the ASEAN Community 2015, becoming one of its own steps to open markets more freely so that the movement of the mobility of goods and services can be channeled properly not only in the country in each of the ASEAN countries, however, can be transferred to all other countries. One of the constraints in this regard is how the readiness of the government of a country in ASEAN to face of fierce competition that will take place freely and openly among various countries so that if not handled properly can result in a fairly high unemployment because the foreign labor which is presented in one of the ASEAN countries is a labor that has a high skill. Therefore, the government must also concern related to the brain circulation phenomenon are able to strengthen the various sectors where the government is able to provide its own facilitieswith the provision of the allocation of funds for research and development and create policies that ensure the products to the convenience of skilled labor to carry out research in homeland then it will strengthen the stability of labor market in ASEAN. Keywords: ASEAN Community 2015, Imbalancing Competition, Brain Circulation, R&D,Stability in ASEAN labor market